Association of COMT Val158Met Polymorphism with Psychopathological Symptoms in Patients with Eating Disorders - Gervasini, G.; Gonzalez, L.M.; Mota-Zamorano, S.; Gamero-Villarroel, C.; Carrillo, J.A.; Flores, I.; Garcia-Herraiz, A. (Current Molecular Medicine, 2018)
Background: Dopamine physiological functions make dopaminergic genes suitable candidates for association studies in eating disorders (ED). A Val158Met polymorphism in the catechol-O-methyltransferase (COMT) gene, which is involved in dopamine degradation, has been studied in relation to ED. Objective: We aimed to analyze the association between this polymorphism and general psychopathological symptoms that are often coupled to these disorders. Method: A total of 303 ED patients, diagnosed according to DSM-5 criteria, completed the SCL-90R questionnaire and were genotyped for the Val158Met polymorphism. Results: There were significant differences in the global indices of the SCL-90R inventory between the three ED groups (Anorexia Nervosa (AN), Bulimia Nervosa (BN) and binge-eating disorder; ANOVA-p < 0.05). Females with BN showed the highest scores (worse symptomatology) of all participants. In this group, a gene-dose effect was observed on the psychometric evaluation of the patients, as Val/Val carriers displayed the highest scores for all the SCL-90R scales, followed by Val/Met and then Met/Met carriers. Significant differences between genotypes were observed in the Obsessive- Compulsive (p = 0.018), Paranoid Ideation (p = 0.0005) and Psychoticism (p = 0.039) scales, as well as in the PSDI (p = 0.014) general index. Conclusion: The results taken together suggest that COMT genetic variability may contribute to general psychopathological symptoms in patients with BN.
Keywords: binge-eating